A Feasibility Study on the Potential Use of Near Infrared Reflectance Spectroscopy to Analyze Meat in Live Animals: Discrimination of Muscles. (14th September 2017) - Roberts, J. J.; Motin, J. Ch.; Swain, D.; Cozzolino, D.
Abstract : Near infrared (NIR) spectroscopy has been proposed as a potential method to analyze different properties in live animals and humans, as infrared light has the ability to penetrate living tissues. This study evaluated the potential use of NIR spectroscopy to identify and analyze beef muscles through the skin nondestructively. The results from this study demonstrated that the NIR region has the potential to noninvasively monitor some properties of meat associated with either fat or muscle characteristics and to differentiate either muscle or fat tissue analyzed through the skin. At present, there are no rapid and noninvasive tools to monitor and assess any characteristic or property in live beef animals. Although these results look promising, more experiments and research need to be carried out before recommending the beef industry using this technology in live animals.